Abstract 24 Improving Cord Blood Unit Selection and Optimizing Manufacturing of a Unique Cord Blood-Derived Product (DUOC-01). (6th September 2022) - Ozamiz, April; Shoulars, Kevin; Noldner, Pamela; Shaz, Beth; Kurtzberg, Joanne
Abstract: Introduction: DUOC-01 are microglia-like cells derived from umbilical cord blood CD14-positive monocytes, which have been shown to induce remyelination in murine models of demyelination. Intrathecal DUOC-01 administration is being tested clinically in two phase I studies. First, DUOC-01 is being tested as a bridging therapy for pediatric patients with inherited leukodystrophies undergoing unrelated donor cord blood transplantation. Second, DUOC-01 is being tested in a phase Ia dose escalation study in patients with primary progressive multiple sclerosis. Objective: DUOC-01 is manufactured from an HLA-matched cryopreserved cord blood unit (CBU). The CBU is thawed and cultured for 21 days under specific conditions, and the resulting DUOC-01 is harvested and formulated with hydrocortisone for intrathecal administration. Cell dosing per patient is limited by DUOC-01 yield, which is highly variable; therefore, there is great need to increase DUOC-01 yield and optimize manufacturing for more consistency. Methods: (1) For the identification of optimal CBU selection, units are screened using small scale DUOC-01 cultures derived from CBU bag segments, which are then scored (0-4). In order to assess the value, we performed screening followed by DUOC-01 manufacturing and correlated the screening score to the DUOC-01 yield. (2) We assessed multiple variables to optimize DUOC-01 manufacturing including media volume and temperature, fetal bovine serum (FBS) lot variability, and culture container material. Results: (1) 5/13 segments scored high (defined as ≥2) while the remaining 8/13 scored low (<2). All 5 high-scored CBUs resulted in high yield (defined as ≥1.6 4 total cells/cm 2 ). Of the 8 low-scored segments, 4 were low yield and 4 were high yield. (2) Comparison of different FBS lots did not show a significant change in DUOC-01 yield. Furthermore, media volume and temperature did not influence product yield. The choice of container material substantially impacted culture yields and cell viability (Figure 1). Discussion: In order to increase cell yield and improve product consistency, we confirmed the value of the CBU segment screening assay and discovered the potential importance of culture container material. More experiments are needed to optimize and finalize product manufacturing.